Inoperable or incompletely resected craniofacial osteosarcoma treated by particle radiotherapy - Seidensaal, Katharina; Dostal, Matthias; Liermann, Jakob; Adeberg, Sebastian; Weykamp, Fabian; Schmid, Maximillian P.; Freudlsperger, Christian; Hoffmann, Jürgen; Hompland, Ivar; Herfarth, Klaus; Debus, Jürgen; Harrabi, Semi B. (Frontiers in Oncology, 2022)
Background To report survival of craniofacial osteosarcoma patients treated by particle radiotherapy. Methods Between January 2010 and December 2021, 51 patients with primary (N = 35) or recurrent (N = 16) inoperable or incompletely resected craniofacial osteosarcoma were treated. In most cases, intracranial infiltration (59%) and macroscopic tumor on MRI/CT (75%) were present. Thirteen had a secondary osteosarcoma (25%). Treatment concepts included combined ion beam radiotherapy (CIBRT, N = 18), protons only (N = 3), carbon ions only (N = 12), IMRT with a carbon ion boost (N = 5), and carbon ion re-irradiation (N = 13). Eighty percent (N = 41) received additionally chemotherapy, most frequently EURAMOS-1 (47%) or EURO-B.O.S.S. (18%). Results The median age was 38, and all patients finished treatment predominantly as outpatients (N = 44). Information on overall survival was available for N = 49 patients. The median follow-up of the survivors was 55 months. For the whole cohort 1-, 2-, 3-, and 5-year overall survival (OS) was 82.8%, 60.4%, 55.2%, and 51.7%, respectively. Those treated by CIBRT (N = 17) demonstrated a superior OS with 92.9% after 1 and 2 years and 83.6% after 3 and 5 years. The median clinical target volume (CTV) was 192.7 and 95.2 cc for the primary and boost plan, respectively. CIBRT, primary diagnosis, age ≤40a, and no macroscopic residual tumor were associated with improved survival in univariate analysis (p = 0.006, p = 0.004, p = 0.002, p = 0.026, respectively), while any foregoing resection compared to biopsy was not identified as a prognostic factor. CIBRT and no macroscopic residual tumor were confirmed as independent predictors of OS on multivariate analysis (HR = 0.107, 95% CI = [0.014, 0.797], p = 0.029 and HR = 0.130, 95% CI = [0.023, 0.724], p = 0.020, respectively). No acute toxicity > grade III was observed. Conclusion CIBRT shows promising results for patients with inoperable or incompletely resected craniofacial osteosarcoma.